2011
DOI: 10.9734/bjmmr/2011/505
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Posttraumatic Stress, Depression and Anxiety among Youths Exposed to a Massive Fire Disaster in Greece

Abstract: Aim: To evaluate the prevalence of symptoms of posttraumatic stress disorder (PTSD), depression and anxiety among children and adolescents exposed to the 2007 fire disaster in Greece along with the relationships of these symptoms with disaster-related stressors and sociodemographic characteristics four months after the fire. Methodology: A sample of 343 youths aged 9-18 years from schools in an area severely affected by the fire completed self-reported questionnaires. The Children's Post-Traumatic Stress Disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Our results are similar to the findings of Annesi (2005), confirming a significant reduction in depression for a treatment group engaged in physical activity compared to a control group who was getting no exercise. The decrease in depression is an important finding especially for children who have been traumatized after disasters (Aslam & Tariq, 2010;Kolaitis, et al, 2011;Roussos, et al, 2005). Some research has found a significant reduction in depression in various training and exercise program (Camero, Hobss, Stringer, Branscum, & Taylor, 2012;Motta, Kuligowski, & Marino, 2010;Bicer, Asghari, Kharazi, & Asl, 2012 (2012) have also demonstrated a significant reduction in students' depression rates through participation in many sports like swimming, track and field, and football.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to the findings of Annesi (2005), confirming a significant reduction in depression for a treatment group engaged in physical activity compared to a control group who was getting no exercise. The decrease in depression is an important finding especially for children who have been traumatized after disasters (Aslam & Tariq, 2010;Kolaitis, et al, 2011;Roussos, et al, 2005). Some research has found a significant reduction in depression in various training and exercise program (Camero, Hobss, Stringer, Branscum, & Taylor, 2012;Motta, Kuligowski, & Marino, 2010;Bicer, Asghari, Kharazi, & Asl, 2012 (2012) have also demonstrated a significant reduction in students' depression rates through participation in many sports like swimming, track and field, and football.…”
Section: Discussionmentioning
confidence: 99%
“…In general, anxiety disorders are the most frequent psychiatric disorders in children, with an increased prevalence of up to 21% (Creswell et al, 2014;Ruiz Sancho & Lago Pita, 2005). Moreover, evidence suggests that stressful situations can trigger psychological distress (Giannakopoulos et al, 2011;Kolaitis et al, 2003). In this regard, confinement has a profound and potentially long-lasting psychological impact; 30% of children isolated or quarantined due to pandemic disasters and subsequent disease-containment responses have reported traumatic stress (Sprang & Silman, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The fires destroyed 1000 houses and 1100 other buildings, and damaged hundreds more. High levels of PTS, depressive and anxiety symptoms (45, 34 and 32%, respectively) were found four months after the disaster in Lakonia prefecture (Kolaitis et al, 2011). …”
Section: Current Research In Greecementioning
confidence: 99%